A parent-directed language intervention for children of low socioeconomic status: a randomized controlled pilot study*. Issue 2 (4th June 2015) - SUSKIND, DANA L.; LEFFEL, KRISTIN R.; GRAF, EILEEN; HERNANDEZ, MARC W.; GUNDERSON, ELIZABETH A.; SAPOLICH, SHANNON G.; SUSKIND, ELIZABETH; LEININGER, LINDSEY; GOLDIN-MEADOW, SUSAN; LEVINE, SUSAN C.
Abstract: We designed a parent-directed home-visiting intervention targeting socioeconomic status (SES) disparities in children's early language environments. A randomized controlled trial was used to evaluate whether the intervention improved parents' knowledge of child language development and increased the amount and diversity of parent talk. Twenty-three mother–child dyads (12 experimental, 11 control, aged 1;5–3;0) participated in eight weekly hour-long home-visits. In the experimental group, but not the control group, parent knowledge of language development increased significantly one week and four months after the intervention. In lab-based observations, parent word types and tokens and child word types increased significantly one week, but not four months, post-intervention. In home-based observations, adult word tokens, conversational turn counts, and child vocalization counts increased significantly during the intervention, but not post-intervention. The results demonstrate the malleability of child-directed language behaviors and knowledge of child language development among low-SES parents.